Proceedings of the 2010 ACM Symposium on Applied Computing 2010
DOI: 10.1145/1774088.1774449
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of database server scalability using an N-tier benchmark with read-intensive workload

Abstract: The performance evaluation of database servers in N-tier applications is a serious challenge due to requirements such as non-stationary complex workloads and global consistency management when replicating database servers. We conducted an experimental evaluation of database server scalability and bottleneck identification in N-tier applications using the RUBBoS benchmark. Our experiments are comprised of a full scale-out mesh with up to nine database servers and three application servers. Additionally, the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Moreover, previous research in multi-tier applications shows that inter-tier network performance typically does not cause significant performance penalty compared to CPU, RAM and I/O utilisation [51,52]. In fact Lloyd et al have empirically shown that for a multi-tier application in a cloud environment, the outgoing and incoming VM network transfer between tiers explain respectively only 0.75% and 0.74% of the overall performance variability.…”
Section: Cpu Load Of the Database Serversmentioning
confidence: 98%
“…Moreover, previous research in multi-tier applications shows that inter-tier network performance typically does not cause significant performance penalty compared to CPU, RAM and I/O utilisation [51,52]. In fact Lloyd et al have empirically shown that for a multi-tier application in a cloud environment, the outgoing and incoming VM network transfer between tiers explain respectively only 0.75% and 0.74% of the overall performance variability.…”
Section: Cpu Load Of the Database Serversmentioning
confidence: 98%
“…We did not consider using an asynchronous event-driven implementation instead [58] that might positively impact performance when carefully tuned [59].…”
Section: Limitationsmentioning
confidence: 99%
“…Previous works [33] have demonstrated that inter-tier network performance typically does not cause significant overheads compared to processor, memory and I/O resources. That is the reason why the Informer module has not been initially designed to gather information about network latencies too.…”
Section: Informermentioning
confidence: 99%